2017
DOI: 10.1177/1535370216685435
|View full text |Cite|
|
Sign up to set email alerts
|

Featured Article: Downregulation of transgelin blocks interleukin-8 utilization and suppresses vasculogenic mimicry in breast cancer cells

Abstract: Vasculogenic mimicry (VM) is an angiogenic-independent mechanism of blood vessel formation whereby aggressive tumor cells undergo formation of capillarylike structures. Thus, interventions aimed at angiogenesis might not target the entire tumor vasculature. A more holistic approach is therefore needed in the development of improved antivascular agents.Transgelin, an actin-binding protein, has been associated with multiple stages of cancer development such as proliferation, migration and invasion, but little is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The detection of TAGLN expression in BT 549 and PMC 42 cells is in agreement with its expression in TNBC tumors and other TNBC cell lines [ 16,33 ] and in the immortalized normal epithelial breast cell lines, MCF10A and MCF12A. [ 13 ] We confirmed the association of TAGLN with the actin cytoskeleton in both cell lines.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The detection of TAGLN expression in BT 549 and PMC 42 cells is in agreement with its expression in TNBC tumors and other TNBC cell lines [ 16,33 ] and in the immortalized normal epithelial breast cell lines, MCF10A and MCF12A. [ 13 ] We confirmed the association of TAGLN with the actin cytoskeleton in both cell lines.…”
Section: Discussionsupporting
confidence: 82%
“…[ 17 ] It also impairs tube formation during vasculogenic mimicry in the TNBC cell line, MDA MB 231. [ 16 ] In contrast, restoration of TAGLN expression inhibits the migration of the colorectal cancer cell lines, DLD1, [ 10 ] and LoVo, [ 8 ] and the bladder carcinoma cell line, TSGH‐8301. [ 36 ] Decreases in migration after TAGLN restoration [ 37 ] as well as after TAGLN silencing, [ 18 ] have been described in different studies of SW480 colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tumoral microenvironment, there is a complex and dynamically interacting areas involving stromal cells (fibroblasts, myofibroblasts, neuroendocrine cells and immune cells), blood vessels, lymphatic network, and ECM (157,158), resulting in a tremendous heterogeneity observed in cancer cells. This condition is because tumor cells express and modulate a broad group of signaling pathways including immune modulatory pathways of cytokines and chemokines, which participate in the progression and establishment of cancer cells (Tables 1, 2) (159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169). In this regard, both cytokines and chemokines induce the expression and activity of MMPs, which in turn allow for the activation of pro-inflammatory signaling pathways as well as the activating receptors, for example, expressed on the surface of T cells and NK cells.…”
Section: Mmps and The Immune System In Cancermentioning
confidence: 99%
“…Wang [33] found that ACSL1 mRNA expression levels were significantly upregulated in clinical breast cancer tissues, and oncoprotein Hepatitis B virus X-interacting protein upregulated ACSL1 in breast cancer by activating transcription factor Sp1. The Aikins study [34] found that transgelin is an actin-binding protein associated with multiple stages of cancer development, such as proliferation, migration, and invasion. The authors studied the role of transgelin in vasculogenic mimicry (VM) and evaluated the effects of VM on endothelial cell-and angiogenesis related-gene expression in MDA-MB-231 breast cancer cells.…”
Section: Copy Number-driven Drug Gene Association Networkmentioning
confidence: 99%